2008
DOI: 10.1111/j.1473-2165.2008.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical tolerance and efficacy of capryloyl salicylic acid peel compared to a glycolic acid peel in subjects with fine lines/wrinkles and hyperpigmented skin

Abstract: SummaryBackground Several chemical agents are currently used to perform superficial peels of the face to reduce facial hyperpigmentation and fine lines/wrinkles. Some of the most commonly used agents are alpha hydroxyl acids, such as glycolic acid (GA), or beta hydroxy acid, such as salicylic acid. Aim This study aims to compare the efficacy of GA to that of a novel derivative of salicylic acid, capryloyl salicylic acid (LHA). Subjects/Methods In a split-face study, 50 female volunteers between the ages of 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 7 publications
0
35
0
1
Order By: Relevance
“…The lipo‐hydroxy variants of salicylic acid have also been shown to deliver skin anti‐aging effects. Capryloyl salicylic acid or 2‐hydroxyl‐5‐octanoyl benzoic acid (LHA) is one of the derivatives of SA that has been recently considered as a safer alternative to Alpha Hydroxy Acids (AHA) and other chemical peels for the reduction of fine lines and wrinkles 48 . Some adverse events (erythema, burning and stinging) were, however, reported during this study, leading to a drop out of 6% of their subjects.…”
Section: Discussionmentioning
confidence: 78%
“…The lipo‐hydroxy variants of salicylic acid have also been shown to deliver skin anti‐aging effects. Capryloyl salicylic acid or 2‐hydroxyl‐5‐octanoyl benzoic acid (LHA) is one of the derivatives of SA that has been recently considered as a safer alternative to Alpha Hydroxy Acids (AHA) and other chemical peels for the reduction of fine lines and wrinkles 48 . Some adverse events (erythema, burning and stinging) were, however, reported during this study, leading to a drop out of 6% of their subjects.…”
Section: Discussionmentioning
confidence: 78%
“…A pilot study [9] . Clinical tolerance and efficacy of capryloyl salicylic acid peel compared to a glycolic acid peel in subjects with fine lines/wrinkles and hyperpigmented skin [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Also notable, 46% of LHA subjects and 34% of the GA subject's demonstrated reduction in hyper pigmentation compared to baseline. The study concluded the 5-10% LHA peel to be as effective as 20-50% GA peel in reducing fine lines/wrinkles and hyper pigmentation suggesting LHA to be a viable alternative [61].…”
Section: Chemical Peelsmentioning
confidence: 96%
“…Deep peels, with increased concentration of TCA solution or phenol, slough the epidermis and papillary dermis and cause inflammation of the reticular dermis. These are reserved for deep wrinkles but increase the risk of scarring and hypo pigmentation [61,62].…”
Section: Chemical Peelsmentioning
confidence: 99%